Cholestasis in Crohn's Disease: A Diagnostic Challenge - Nir Hilzenrat; Esther Lamoureux; Averell Sherker; Albert Cohen (Canadian Journal of Gastroenterology)
A 24-year-old male with Crohn's disease who developed three independent episodes of cholestatic liver disease over an eight-year period is described. The first episode was related to an idiosyncratic drug reaction while on sulfasalazine. The second episode, at the time of an exacerbation of his colitis, was characterized by moderate portal inflammation on liver biopsy and resolved quickly while he was on corticosteroid therapy. The most recent episode, occurring when the bowel disease was quiescent, was due to granulomatous hepatitis and resolved clinically with no specific therapy. Because numerous potentially serious hepatobiliary complications have been associated with inflammatory bowel disease, prompt and aggressive investigation in these instances is recommended.